Immunological Role of Megakaryocytes and Platelets during Influenza A Virus Infection - Rahman, Fryad M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
Influenza viruses pose a serious threat to public health, with severe cases often characterized by lung damage and inflammation. However, the underlying mechanisms of these processes remain poorly understood. This study aimed to investigate the essential role of megakaryocytes (MKs) and platelets (PLTs) in influenza A virus (IAV) infections. Conducted at the Department of Rare Respiratory Diseases, Cystic Fibrosis, and Pulmonology, Nord University Hospital, Marseille, France, the study collected seventy blood samples between October 2018 and March 2019. Samples were obtained from healthy individuals and patients diagnosed with IAV. Messenger RNA was extracted from isolated PLTs and subjected to quantitative real-time-polymerase chain reaction using sets of primers targeting immune marker genes. Western blot analysis was also performed for confirmation, focusing on Fas Ligand (FasL). Results showed that PLTs from IAV-infected individuals expressed the FasL, tumor necrosis factor-related apoptosis-inducing ligand, and Granulysin (GNLY) receptors when activated. Furthermore, an in vitro assay revealed the presence of FasL receptors on infected CMK cell lines. In vivo investigations demonstrated that activated MKs and PLTs in mice also expressed FasL. Interestingly, none of the immune receptors under investigation were found in both MKs and PLTs in mouse model studies. In conclusion, MKs and PLTs play a significant role in influencing immune responses that may help prevent viral spread during infection. However, further examination of their mechanisms of action is warranted. Understanding the involvement of these cells in influenza pathogenesis could offer valuable insights for developing potential therapeutic strategies.